INTRODUCTION IN SOCIAL SCIENCE RESEARCH ARTICLES BY INDONESIAN AUTHORS: A COMPARATIVE MOVE ANALYSIS - Kurniawan, Eri; Nabilla, Siti Nurzihan; Mauludini, Yalma Rifqiya (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
The introduction section of a research article (RA) is crucial, as it serves as the foundation for the entire research study. A well-crafted introduction can captivate readers, offering essential insights into the background and rationale for the study, while also conveying the research's quality and reliability. This study investigates how novice versus experienced social science researchers introduce their work in English research articles (RAs) published in internationally recognized Scopus-indexed journals compared to those published in Indonesian national journals. We analyze the rhetorical structure and linguistic features used in these introductions. Employing Swales' (2004) Create A Research Space (CARS) model as a theoretical framework, this descriptive comparative qualitative study delves into the analysis of commonalities and differences in the execution of rhetorical moves and steps, as well as linguistic features and metadiscourse. The results reveal that both sets of data exhibited all three rhetorical moves outlined in the CARS model, namely Move 1 (Establishing a Territory), Move 2 (Establishing a Niche), and Move 3 (Presenting the Current Work). However, the findings also underscore distinctions in how these steps and metadiscourse were realized, indicating that writers in both groups employed distinct approaches when introducing their research studies. Implications to English teaching at universities and publication workshops are discussed.